Entre o trote dos cavalos e o ronco dos motores: os trabalhadores do setor de transportes urbanos de Santa Maria no pós-abolição (1898 – 1937) - Rodrigues, Luiz Fernando dos Santos da Silva (2024)
The present work aims to study the experiences of carters, coachmen and chauffeurs from Santa Maria during the First Republic, intersecting the categories of race and social class, in addition to understanding the constitution of the urban transport sector in that period. We will problematize the post-Abolition period, taking as a starting point the trajectories of black workers. It was possible to observe the agency of those subjects, many former slaves and other descendants of formerly enslaved people, who sought better working and existence conditions in Santa Maria, in a context marked by precariousness and racism, which emerges as a historical problem. We will also investigate the conflicts, solidarities and organization among those workers, which also attracted our attention to the different types of associations in which those subjects were involved – both class organizations and black associations in the city. The articulations between the Santa Maria transporters, many of them black, open up space for us to reflect on a problem in the historiography of work in Brazil, which is the existence of a “historiographic wall” that prevents dialogue between the History of Labor and the History of Slavery and Post-Abolition – a wall that has been overcome in recent years, through a historiography increasingly committed to understanding black experiences in the world of work. Black workers did not disappear with the signing of the golden law, much less were they “replaced” by European immigrants. The processes unleashed in the last decades of the 19th century made possible an endless number of strategies adopted by the black population of Brazil, denoting the visions of freedom, expectations, frustrations, in short, the experiences of social agents, among them the cart drivers, hitchhikers and chauffeurs of Santa Maria which will appear on the following pages.